Management of malignant pleural mesothelioma—The European experience - Opitz, Isabelle (Pioneer Bioscience Publishing Company, 2014)
Management of malignant pleural mesothelioma (MPM) remains a clinical challenge and the incidence of the disease will continue to increase worldwide. Several aspects of mesothelioma treatment are discussed controversially, in particular, regarding extent and best type of surgery, radiotherapy, and the role of neoadjuvant or adjuvant treatment. However, best survival data is reported from groups using multimodality treatment including macroscopic complete resection (MCR) achieved by either extrapleural pneumonectomy (EPP) or (extended) pleurectomy/decortication for patients qualifying from the tumor biology, stage, and patient’s performance status and comorbidities. Several aspects have to be considered during surgery but morbidity and mortality have been reduced at experienced centres. The final analysis of extended selection algorithms is pending.